Impact of spirituality on work-to-home interface and turnover intention among physicians in Nigeria - Jonathan, Vem Linus (2016)
People are important asset in every organization be it public or private. They become even more strategic when they are retained, as doing so benefits an organization in numerous ways namely, (1) developing and retaining knowledge base that spawns innovative thinking, (2) reduces the cost of talent hunt and opportunity lost, (3) ensuring sustainable competitive advantage and (4) increasing employee loyalty and citizenship behaviour. Employee turnover phenomenon has been a subject of great concern among practitioners, and a repeated phrase in academic research due to its persistent resurgence in unpredictable manner. Despites the hegemony established in previous studies between predictors such as job satisfaction, emotional exhaustion, organizational support and many others with turnover intention, the problem still remains. Spirituality renaissance in recent times has opened up new frontier in Human Resource Management and Psychological research in the quest for superior explanation to this challenge. In the midst of the burgeoning research on spirituality, so many perspectives have emerged. This study was conducted among 290 physicians working in Nigeria’s tertiary and secondary health institution, in view of the high rate of turnover bedevilling the sector in spite of the poor health care development indices. Riding on Matter-Formism Theory of existence to underpin the conceptual relationship, and other supporting theories such as Role Expansion, Spill-over and Social Exchange Theory, a number of testable hypotheses were developed to fill the three research gaps identified. These include the need to empirically test the construct spirituality characteristics to determine its effects in predicting physician’s turnover intention. Furthermore, lack of literature on the interaction between spirituality and work-to-home interface to address turnover intention holistically was identified. In addition, study realizes dearth of research on the undesirable aspect of spirituality which it intends to assess if perceived organizational support and spiritual intelligent play the role of moderators in the relationship between spirituality characteristics, work-to-home interface. On the course of this, four research objectives were developed to include (1) assessing the relationship between spirituality characteristic and turnover intention, (2) to determine the mediating role of work-to-home interface in the relationship between spirituality characteristics and turnover intention. (3) to ascertain the extent to which perceived organizational support (POS) moderates the relationship between spirituality characteristic and work-to-home interface and (4) to ascertain the extent to which spiritual intelligence (SI) moderates the relationship between spirituality characteristic and work-to-home interface. Analyses were conducted using PLS-SEM, and the results revealed that, Spirituality Characteristics relates indirectly with Turnover intention, through the mediating role of Work-to-Home interface. Furthermore, Perceived Organizational Support (as external factor) moderate the relationship between Spirituality Characteristics and Work-to-Home Resources and Demand, likewise Spiritual Intelligent (as internal factor) was found to moderate the relationship between Spirituality Characteristics and Work-to-Home Resources and Demand. Based on the results, a number of contributions were inferred in relation to theoretical, practical and policy aspect to cope turnover intention in Nigeria’s health sector.